Application of means-end chain model in architectural research - Mohd. Jusan, Mahmud (Penerbit UTM, 2008)
The core of architectural education is the design studio which focuses on the practical "hands-on" aspects of learning in this area. The most important place for students to apply the learned theoretical knowledge along with creativity is in the architecture studio. The manner in which the architecture studio is able to meets its objectives as a learning environment for students is resultant of the person-environment congruence (PEC) relationship. This article focuses on the studio's features as it relates to the user's preferences, which are influenced by personal values utilizing the Means-End Chain (MEC) model of research. Research conducted with 25 students via laddering interview brought out sixteen (16) key studio attributes. These findings reflect a distinct direction for design reference which relates to the design features of architecture studio to the personal values expressed. In that case, designers are able to make conscious design decisions which support the redefinition of the studio as the most important learning space in architectural education .